Perancangan Media Terapi Menggunakan Virtual Reality Dengan Metode Desensitisasi Untuk Penderita Fobia Hewan - Naufal Janitra Kyrana; Muhammad Yasser Arafat (CV. Multi Kreasi Media, 2023)
Phobia is a type of anxiety disorder that shows an expression of irrational fear and interferes with the life of an individual, personally or socially. Long-term phobia can cause its sufferers to experience stress and depression because of the things they fear. This research aims to make the medium of therapy by using virtual reality with systematic desensitization therapy for people with phobia of animals, and developed on an android platform. The use of the systematic desensitization therapy is to direct the subject into situations that raise their fears, under a very safe and controlled situation. The research method used here is qualitative method. Research data are collected by using observation, interviews and library research methods. The software development method used is the waterfall method, and the testing method used is Black Box and White Box testing. The output of this research is expected to assist people with phobia of animals in doing therapy, find out the level of fear of people with phobia of animals and reduce cases of phobia of animals as well.